Comparación entre la cuantificación de la Glucosa mediante la Glucometría Colorimétrica y la Glucometría Digital en pacientes Diabéticos, Iquitos, Julio-Enero 2016 - Perea Vargas, Rosa María (2018)
Abstract Introduction: The present study aims to compare the quantification of glucose by colorimetric and digital glucometry, used for the blood glucose self-monitoring, in diabetic patients from Iquitos between July 2015 and January of 2016. Through parameters such as accuracy, precision and linearity of both methods. Methods: The glucose was measured in capillary by a digital glucometer (Accu-chek®) and the reference method (colorimetry) respectively. The accuracy, precision and linearity of both methods was determined. Results: Accuracy (r = 0.963 and R2 = 0.928), precision (variation = 7.61%, 4.52%; digital and colorimetric glucose measurement respectively) and linearity (R2 = 0.998 in both methods) were determined. Conclusion: The slope is same in the digital method (y = 7.36 + 0.96 * x) than the colorimeter method (y = 0.19 + 0.99 * x).